2008
DOI: 10.1002/cncr.23339
|View full text |Cite
|
Sign up to set email alerts
|

Liver disease induced by radioembolization of liver tumors

Abstract: Primary plasma cell leukemia (pPCL) is a rare, yet aggressive form of de novo plasma cell tumor, distinct from secondary PCL (sPCL) which represents a leukemic transformation of pre‐existing multiple myeloma (MM). Herein, we performed a comprehensive molecular analysis of a prospective series of pPCLs by means of FISH, single nucleotide polymorphism (SNP) array and gene expression profiling (GEP). IGH@ translocations were identified in 87% of pPCL cases, with prevalence of t(11;14) (40%) and t(14;16) (30.5%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
243
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 335 publications
(265 citation statements)
references
References 46 publications
5
243
2
7
Order By: Relevance
“…Their results provide reasoning to the D NL threshold noted in other clinical studies of 70 Gy using GMS [44] and approximately 40-50 Gy using RMS [13,45]. It should be noted that although no toxicity was noted with absorbed doses of up to 100 Gy [46], the manufacturer of RMS recommends a D NL of 80 Gy, and a recent summary suggests a preferable D NL of 50 Gy [29].…”
Section: Differences Between Rms and Gmssupporting
confidence: 59%
“…Their results provide reasoning to the D NL threshold noted in other clinical studies of 70 Gy using GMS [44] and approximately 40-50 Gy using RMS [13,45]. It should be noted that although no toxicity was noted with absorbed doses of up to 100 Gy [46], the manufacturer of RMS recommends a D NL of 80 Gy, and a recent summary suggests a preferable D NL of 50 Gy [29].…”
Section: Differences Between Rms and Gmssupporting
confidence: 59%
“…This index takes values between 0.5 (discriminator no better than random) and 1 (perfect discrimination). Interpretation is similar to the area under the curve (AUC) or C-index for binary responses, indicating the probability that the predictions for a random pair of subjects are concordant with their outcomes [17].…”
Section: Discussionmentioning
confidence: 80%
“…Crudely speaking, the lower number of glass spheres gives a less uniform irradiation, which is associated with reduced toxicity, which makes tolerable a three times higher mean parenchyma absorbed dose. This argument and calculation explains why clinical studies have shown that higher mean absorbed doses can be tolerated with glass microspheres than with resin microspheres (70 Gy averaged over the whole non tumoral liver in Child A HCC patients for glass microspheres [19], versus about 40 Gy for resin microspheres [20][21][22][23]). …”
Section: Clinical Importance Of the Difference In The Number Of Micromentioning
confidence: 99%